PENGARUH KUALITAS PELAYANAN DAN KUALITAS PRODUK TERHADAP KEPUTUSAN KONSUMEN MENGGUNAKAN JASA ANJANI CATERING DI TENGGARONG - ., Adi Yatma (EKONOMIA, 2013)
Adi Yatma, 2013, Service Quality Analysis Product Quality Influence Consumer Decision Against Using Anjani Catering Services In Tenggarong, under the guidance of Mr. and Mrs. Jonathan Robin Mardiana.The purpose of this study was to determine the effect of product quality and service quality on consumer decision choosing Anjani Catering services in Tenggarong.Basic theory used is the Marketing Management by using a multiple linear regression analysis with 30 samples.The results showed:1. Corelatian value (R) of 0.857, which means the variable quality of product and service quality has a very close relationship to consumer decision choosing Anjani Catering services in Tenggarong it also means that the independent variable variable product quality and service quality can be used as an estimator of the decision of consumers choose Catering services in Tenggarong Anjani. 0.734 indicates that the variable quality of product and service quality have an influence on consumer decision choosing Anjani Catering services in Tenggarong (Y) of 73.4%, while the remaining 26.6% influenced by other variables not included in this study2. F value calculation 37.199> F table 2.15 and 0.000 significance <0.05, which means also jointly variable product quality and service quality has a significant influence on consumer decision choosing Anjani Catering services in Tenggarong. Thus, the hypothesis put forward is suspected that factors of product quality and service quality jointly influence the consumer decision choosing Anjani Catering services in Tenggarong, accepted.3. Â Logistic regression calculation Y = 0.330 + 0.340 X1 + 0.566 X24. Standdarized beta coeficient value variable product quality 0.338, smaller than the beta coeficient standadrized variable service quality 0.653, so the hypothesis that states alleged dominant influence on product quality consumer decision choosing Anjani Catering services in Tenggarong (Y) is rejected.Â Keywords: Quality Products, Quality Service - Consumer Decision